NurseÂ´s activities at the family health program when care of Parkinson’s disease in Lagarto-SE - Cavalcante, K. M. H; dos Santos, R. K. C.; TimÃ³teo, P. E. S. (Scientific Electronic Archives, 2018)
Parkinson’s disease (PD) is a neurological disorder resulting from the degeneration of black brain cells, compromising the autonomous movements of the human body. The signs and symptoms triggered by PD have negative consequences for the patient and his family, bringing greater demand to the health services. Thus, it is the responsibility of the health team, including the nursing team, to provide support to these patients. Therefore, it was aimed to identify the performance of the nurse of the PSF of the city of Lagarto-SE in the care given to these patients. This is a descriptive and qualitative research. Participants were 10 nurses from 09 Basic Health Units. Data were obtained through a questionnaire related to nursing care provided to patients with PD and their relatives. The qualitative data analysis was performed according to the Bardin content analysis steps. It was possible to observe only two records of patients with PD. It was noted that some of the interviewees are aware of the care that should be provided to these patients and their relatives, but they identify important flaws. It was also identified possible difficulties faced in the care of patients with PD and suggestions from the participants to improve this care.